The Association of a Lower Risk of Fibromyalgia with Human Papillomavirus Vaccination: A Retrospective Cohort Study from the TriNetX US Collaborative Network - Lin-Hong Shi; An-Ping Huo; Shiow-Ing Wang; Pui-Ying Leong; James Cheng-Chung Wei (Vaccines)
Objective: Remarkably similar symptoms have been observed between fibromyalgia patients and those who present adverse events after HPV vaccination. However, no research has been conducted on their association. Methods: Using data from the US collaborative network within the TriNetX network, we identified all the females who had had an HPV vaccination within 1 year before an index date falling between 2016 and 2023. We selected a propensity-score-matched (PSM, 1:1 ratio), non-HPV-vaccinated cohort as the comparator. Both cohorts were followed up from 1 day after the index date until the diagnosis of incidental fibromyalgia or until the patient was lost to the follow-up process or until the end of 2023. Results: After PSM, a total of 421,564 females in the HPV-vaccinated cohort and 421,564 females in the non-HPV-vaccinated cohort were included in the study. Significantly lower risks of developing fibromyalgia after 5 years’ follow-up were consistent in different models after adjusting for different covariates (adjusted hazard ratios [aHRs]: 0.505, 0.665, and 0.601). Also, significantly lower risks of incident fibromyalgia were identified across different follow-up periods, namely, 1 day to 1 year (HR: 0.464; 95% CI, 0.386–0.559), 1 day to 3 years (HR: 0.553; 95% CI, 0.494–0.618), 1 day to 5 years (HR: 0.601; 95% CI, 0.549–0.658), and 1 day to 7 years (HR: 0.636; 95% CI, 0.587–0.690). Conclusions: This study demonstrates that HPV vaccination significantly decreases the risk of developing incident fibromyalgia across different follow-up periods and subgroups. Our study suggests that HPV vaccination may potentially reduce the risk of developing fibromyalgia in female patients, which needs validation through studies of the mechanisms involved.